Implementing the Principle of Transparency to Realize Good Governance in Village Government - Suriani, Suriani; Sumardi, Lalu; Kurniawansyah, Edy (Jurnal Penelitian Medan Agama, 2025)
The implementation of good governance is the goal of every government administrator, including in village government. An important aspect in realizing good governance is the existence of openness or transparency of the government to the community as regulated in Law Number 6 of 2014 concerning Villages. Good governance itself is a system of policy and institutional values that prioritizes openness. In line with that, based on the results of the study, the implementation of the principle of openness in Sukaraja Village has begun to be implemented, especially in terms of delivering development information and village financial management. However, there are still several obstacles such as lack of community participation and the lack of use of social media, these obstacles become challenges for the village government in implementing the principle of openness to realize good governance village government. This study uses a qualitative approach with a case study type with data collection techniques namely observation, interviews and documentation. In order to reduce misunderstandings from the community towards the Sukaraja village government, it is necessary to implement the principle of openness to realize good governance village government.